Managing Paediatric Growth Disorders: Integrating Technology Into a Personalised Approach - Jenny Child; Christine Davies; Katie Frost; Eleanor McDermid; Rachel Pidcock; John Weinman; Martin O. Savage (Galenos Yayincilik, 2020)
Long-term growth management can be challenging for patients, families and healthcare professionals (HCP). Personalised optimal responses to growth hormone (GH) therapy depend on the creation of a good working relationship between the patient and family and the HCPs responsible for care. Current unmet needs in growth management will be discussed, focusing on the likelihood of a poor growth response and its identification and management with emphasis on the importance of good adherence to GH therapy. Digital tools are now available to record injections and communicate accurate adherence data to the HCP and patient. Psychological barriers to good adherence will be covered, with techniques identified to change behaviour and improve outcome. Motivational interviewing is a valuable skill in this respect and should be taught to both medical and nursing HCPs to enhance the quality of the relationship with the patient and family. Key messages are, firstly, the importance of personalised care with the HCP using acquired psychological skills to prevent and manage poor adherence. Secondly, a human-eHealth partnership is necessary to maximise the benefit of new digital tools to aid in successful growth management.